ANALISIS PENERAPAN STRATEGI YANG INOVATIF PADA PEMBELAJARAN IPA SD SDN DUKUH 08 PAGI - Shupaeroh, Hanna Yasmin; Hana Nur Hafidhah; Masrofah Tri Nurhayati; Nabillah Khairunnisa; Prima Mutia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the effectiveness of hands-on science teaching methods in a fourth-grade classroom. Focusing on the concept of energy, the study utilizes observation and interviews as primary research instruments to gather data on students' learning experiences and outcomes. The research method involves qualitative analysis, specifically examining how practical experiments and group discussions contribute to students’ understanding of scientific concepts. Findings indicate that hands-on learning and group-based activities significantly enhance students’ engagement and comprehension of complex ideas by allowing them to witness real-life applications of theoretical knowledge. Challenges, such as varying student learning capabilities, occasionally limit the effectiveness of this method. To address these issues, the teacher adapts the instruction by providing additional support to students with difficulties and reviewing concepts as necessary. Overall, the study suggests that hands-on, project-based learning fosters a deeper understanding of science, while adaptive teaching strategies are crucial to meeting diverse learning needs.